Stochastic finite-time stabilization for discrete-time positive Markov jump time-delay systems. Issue 1 (January 2022) - Liu, Li-Juan; Zhang, Xuesong; Zhao, Xudong; Yang, Bin
Abstract: In this paper, the problems of stochastic finite-time stability and stabilization of discrete-time positive Markov jump systems are investigated. To deal with time-varying delays and switching transition probability (STP), stochastic finite-time stability conditions are established under mode-dependent average dwell time (MDADT) switching signal by developing a stochastic copositive Lyapunov-Krasovskii functional approach. Then a dual-mode dependent output feedback controller is designed, thus stochastic finite-time stabilization is achieved based on linear programming technique. Finally, two examples are given to show the effectiveness of our results.